"Periosteum: An imaging review". (2020) - Maia Ferreira Alencar, Carlos Henrique; Sampaio Silveira, Cláudio Régis; Cavalcante, Matheus Martins; Maia Vieira, Clarissa Gadelha; Diógenes Teixeira, Manoel Joaquim; Neto, Francisco Andrade; de Abreu, Armando; Chhabra, Avneesh
Highlights: The periosteum has different characteristics between genders and age groups, and may change with the use of medications. Conventional plain radiography can often determine the aggressiveness of periosteal reactions. Knowledge of the periosteum's anatomy eases the understanding of its periosteal reactions. Systemic periosteal reactions are generally underdiagnosed, due to compartmentalized analysis. Abstract: Periosteum is a fibrous sheath, coating the external bone, except in the articular surfaces, tendon insertions and sesamoid bone surface¹. It changes its aspects and characteristics with aging, becoming progressively less elastic and more firm. It is composed of two different layers: outer fibrous (firm, collagen-filled) and inner proliferative (cambium, containing osteoprogenitor cells) ² . Four vascular systems are responsible for the blood supply of the periosteum: the intrinsic periosteal system, located between fibrous and proliferative layer; the periosteocortical, the main nutritional arteries of the periosteum; the musculoperiosteal, responsible for the callus formation after fractures; the fascioperiosteal, specifically for each bone.³ It is crucial to bone formation and resorption, reacting to insults in the cortical bone, such as tumors, infections, traumas, medications and arthritic diseases. The aggressiveness of the reaction can be suggested by its radiological aspect and appearance 4 . The periosteum in children is looser compared to adults, resulting in earlier and more exuberant reactions. All these aspects will be detailed, so the essential information all radiologists need to know will be discussed.